KMP01D Demonstrates Beneficial Anti-inflammatory Effects on Immune Cells: An ex vivo Preclinical Study of Patients With Colorectal Cancer - Gasser, Martin; Lissner, Reinhard; Nawalaniec, Karol; Hsiao, Li-Li; Waaga-Gasser, Ana Maria (Frontiers in Immunology, 2020)
Background: Colorectal cancer (CRC) is frequently associated with dysbiosis of the gut microbiome which, together with a compromised gut barrier, can result in perioperative endotoxin leakage into circulation. Constant local and systemic inflammatory activity is suggested to facilitate metastases formation. Previous studies have pointed to the capacity of a colostrum preparation to neutralize endotoxins within the gastrointestinal tract which could ameliorate associated inflammatory responses and tumor recurrence in affected patients. This study aimed to examine effects of the colostrum preparation, KMP01D, on the inflammatory activity of patient-derived immune cells. Methods: The effects of KMP01D on pro-/anti-inflammatory cytokine responses and apoptosis were examined ex vivo using immune cells from CRC patients (stage I-IV, n=48). The expression of CD14, CD68, Toll-like Receptor(TLR)4, and Insulin-like Growth Factor(IGF)-1 was also analyzed. Results: KMP01D increased Interleukin(IL)-10 and IL-13 anti-inflammatory cytokine expression in patient-derived peripheral blood mononuclear cells (PBMCs). Interestingly, KMP01D also decreased secretion of IL-1β, IL-6, Interferon(IFN)-γ, Tumor Necrosis Factor(TNF)-α, IL-12 inflammatory cytokines and IGF-1 in these cells. Moreover, CD14 and TLR4 expression involved in endotoxin signaling was downregulated in PBMCs and tumor-derived cells. Apoptosis of immune cells and tumor-derived cells was likewise enhanced with KMP01D. Addition of vitamin D3 as a co-factor demonstrated enhanced anti-inflammatory effects. Conclusions: KMP01D demonstrated beneficial ex vivo effects on inflammatory cytokine responses in PBMCs and enhanced apoptosis of immune cells from CRC patients. In line with previous clinical trials, we present new evidence endorsing KMP01D as a treatment strategy to regulate stage-dependent local and systemic inflammation in CRC patients.